Dilemmas in the study of information: exploring the boundaries of Information Science, de S. D. Neill - Mueller, Suzana Pinheiro Machado (Revista de Biblioteconomia de Brasília, 1997)
NEILL, S. D. Dilemmas in the study of information: exploring the boundaries of Information Science. Westport, Conn.: Greenwood Press, 1992. xv + 184 p. (Contributions in Librarianship and Information Science, 70).